1996
DOI: 10.1111/j.1476-5381.1996.tb15235.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl‐11‐keto‐β‐boswellic acid (AKBA): structure requirements for binding and 5‐lipoxygenase inhibitory activity

Abstract: 1 5-Lipoxygenase (5-LOX) products from endogenous arachidonic acid in ionophore-stimulated peritoneal polymorphonuclear leukocytes (PMNL) and from exogenous substrate (20 gM) in 105,000 g supernatants were measured. 2 The effects of natural pentacyclic triterpenes and their derivatives on 5-LOX activity were compared with the inhibitory action of acetyl-l -keto-p-boswellic acid (AKBA), which has been previously shown to inhibit the 5-LOX by a selective, enzyme-directed, non-redox and non-competitive mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 13 publications
1
97
0
3
Order By: Relevance
“…The antiinflammatory effect of Boswellia may be due to 3-Oacetyl-11-keto-β-boswellic acid, which is the most active component of Boswellia extract and has been demonstrated to be a potent inhibitor of 5-Lipoxygenase (5-LOX), which is a key enzyme in the biosynthesis of leukotrienes (LTs) from arachidonic acid in the cellular inflammatory cascade. 37 The second model used in this work is RIR injury. It is a major cause of acute renal failure and renal graft rejection and may lead to CRF if chronic.…”
Section: Discussionmentioning
confidence: 99%
“…The antiinflammatory effect of Boswellia may be due to 3-Oacetyl-11-keto-β-boswellic acid, which is the most active component of Boswellia extract and has been demonstrated to be a potent inhibitor of 5-Lipoxygenase (5-LOX), which is a key enzyme in the biosynthesis of leukotrienes (LTs) from arachidonic acid in the cellular inflammatory cascade. 37 The second model used in this work is RIR injury. It is a major cause of acute renal failure and renal graft rejection and may lead to CRF if chronic.…”
Section: Discussionmentioning
confidence: 99%
“…Many PTs (including UA, OA, amyrin), but not 4-ring compounds, bind to 5-LO protein. However, only PTs from the BA series possessing an Il-keto group in addition to a hydrophilic function at C-4 exert potent 5-LO inhibitory activity (26)(27)(28). GA was reported to be active in ionophore-stimulated cells, although this action was attributed to inhibition of PLA2 (29).…”
Section: Hydrolytic Enzymesmentioning
confidence: 99%
“…It was suggested that AKBA 89 acts at a selective binding site of 5-LO for various PTs that is different from the AA-binding cleft [155], where certain functional groups (i. e., the 11-keto and C-4-carboxylic moiety) are essential for 5-LO inhibitory activity [166]. Although previous reports demonstrated a selectivity of BAs for 5-LO, we recently showed that AKBA 89 potently suppresses 12-LO product formation, with even higher potency in cell-free assays (IC 50 = 15 mM) as compared to 5-LO (IC 50 = 50 mM) [167].…”
Section: Pentacyclic Triterpenesmentioning
confidence: 99%